The Influence of Groupthink and Bounded Rationality in Decision-Making on Public Policy - Aemillianus Yollan Permana; Nur Wening (Eduvest - Journal of Universal Studies, 2024)
In public policy, the decision-making process can be influenced by several factors, including groupthink and bounded rationality. However, decision making must still be done with a systematic approach, thinking, and choosing the alternative with the lowest risk from the existing alternatives. Decision making without careful consideration, especially regarding public policy, will be very vulnerable to public criticism because it has political content and is related to the interests of many people. Based on literature studies, the existence of groupthink and bounded rationality can have a positive or negative influence on the decisions taken. This research is to describe the influence of groupthink and bounded rationality on decision making, the results show that groupthink and bounded rationality can influence decision making. Groupthink can influence positively and negatively in the decision-making process. The positive influence can improve group performance and show better results, while the negative influence limits people's thinking, power hierarchies and leadership pressure. Bounded rationality can cause bias in decision making.